Analysis of Singing Methods in Memorization Learning of Vocabulary at MA Ma'arif Roudlotut Tholibin Metro | Analisis Metode Bernyanyi dalam Pembelajaran Hafalan Mufrodat di MA Ma’arif Roudlotut Tholibin Metro - Anjarwati; Syaifullah, Muhammad; Oktafia, Anita (NAJAH BESTARI, 2024)
A method is a prerequisite for achieving a goal, without a method the goal is achieved will not be accomplished well, singing is regarded as a guide to speaking. One of the techniques used in delivering learning material. The singing method is one of the ways to communicate with students so that the learning process in the classroom is more effective, therefore the method of singing is essential in the teaching learning process. This research uses qualitative methods so that the author can describe in detail the use of the methods in the first lesson of the Ma'arif Roudlotut Tholibin MA, Data collection techniques using observations, interviews and documentation. The results of this singing is to increase the confidence of a student in demonstrating his ability in learning, to make the student more happy and active in the learning process, and to make it easier for the student in memorizing of vocabulary.